Genetic Diversity and Connectivity of Sea Urchin Tripneustes gratilla in Region Surrounding Cenderawasih Bay, Papua-Indonesia and Indo-Pacific - Abdul Hamid A. Toha; Ambariyanto Ambariyanto; Widodo Widodo; Luchman Hakim; Sutiman B. Sumitro; Agustina L. N. Aminin (HAYATI Journal of Biosciences, 2022)
Cenderawasih Bay has extremely high biodiversity with an enormous amount of endemic species due to geography isolation. Tripneustes gratilla is one of the species that is abundant in the bay. The species has ecological value that is suitable for bio-indicators of the environmental condition. Since the Bay relatively isolated area, then we examined the impact of the geographical conditions on genetic diversity and connectivity of Tripneustes gratilla among populations in the region surrounding Cenderawasih Bay based on the mitochondrial cytochrome c-oxidase-1 gene. Results of the study showed that genetic variation of the species within the population is high; despite the genetic variation among populations was low. The data suggested that the entire population of T. gratilla were closed connected, homogeneous, and shared polymorphic profile. Then we assumed the gene flow occurred for a long time among populations without geographical barriers. This information is a warrant to develop an effective strategy to maintain biodiversity in the Cenderawasih Bay.